"An analytic assortment of diet and dalliance in Srotodushti with special reference to Jwara" A review study - Shalinee Kumari Mishra; Vd. Kamalesh Kumar Sharma; Dharmendra Mishra (Wolters Kluwer Medknow Publications, 2022)
Objectives: To identify and explore the Apathya and Pathya according to the Srotasa in Jwara. Data Source: Charak Samhita Vimana Sthana and Charaka Samhita Chikitsa Sthana, available all Sanskrit commentaries on Charak Samhita, and other commentary on Astanga Sangrah and Astanga Hridaya Samhita. Review Methods: Profound explorative review study of all collected material using offline and online available texts. Result and Conclusion: One year old Cereals and pulses, husked grains Mudga (Phaseolus aureus), Jeevanti, Solanum nigram, (Kakamachi), Corchorus capsularis, Centella asiatica (Brahmi), (Mandukaparni), Trichosanthes dioica (Patola) are some vegetable and dietary substance to be used.